Preparation and mechanical characterization of natural polymer composite material obtained from fox tail palm seeds - Kolakoti, Aditya; Geeri, Satish; Rochman, Muhammad Latifur; Setiyo, Muji (Universitas Mercu Buana, 2024)
This experimental investigation reveals the preparation of natural composite material from foxtail palm tree seeds. The fruits from the foxtail palm tree are used for the extraction of oil, and the by-product of the extraction process is freely dumped. This study attempts to utilize the waste by-product of foxtail palm tree fruit as a valuable natural composite material. The fabrication was done using the hand lay-up method for the proposed reinforcement (4% and 8%) of filler materials. The obtained composite materials are subjected to significant mechanical characterization of tensile behaviour, flexural property, and hardness. In addition, the morphological study was also carried out by the scanning electron microscope (SEM). The results show that, as the reinforcement percentages of filler material increase, the mechanical properties are improved. This may be due to the uniform dispersion of natural fibres in the polymer. The tensile strength was improved by 22.43% and 29.08% for 4% and 8% filler reinforcement. Similarly, the stiffness property was improved by 9.32% for 4% reinforcement and 18.68% for 8% reinforcement when compared with neat composite. The SEM images reveal the failure analysis, bonding strength and fibre pull-out in the composites. Finally, the foxtail fruit fibre shows promise as a reinforcing agent in composite materials, improving their mechanical properties and making them suitable for various applications requiring strength, stiffness, and resistance to deformation.